Species classification and novel plasmid identifications in Arcobacter cryaerophilus and Arcobacter cryaerophilus-like organisms - Zhou, Guilan; Wang, Min; Wang, Hairui; Chen, Xiaoli; Gu, Yixin; Shao, Zhujun; Zhang, Jianzhong; Zhang, Maojun (Frontiers in Microbiology, 2022)
The Arcobacter is a globally emerging foodborne and zoonotic pathogen that can cause diarrhea in humans. It is relatively homogenous and clearly distinguishes the group from other Epsilonproteobacteria. Arcobacter cryaerophilus (A. cryaerophilus) is a heterogeneous species and little is known about its genomic characterization in China. This study aims to determine the genetic and plasmid features of A. cryaerophilus based on whole-genome sequence (WGS). Average Nucleotide Identity (ANI) and in silico DNA–DNA hybridization (isDDH) were used for the species classification for 90 initially identified A. cryaerophilus strains. One complete genome and 42 draft genomes were obtained by whole genome sequencing. The genomic characteristics were determined using various bioinformatics software. The genomes of the strains examined were estimated to vary from 1.81 to 2.28 Mb in length, with a G + C content of around 27%. ANI and isDDH results indicated that 90 initially identified A. cryaerophilus strains should be reclassified into four new species (ANI > 96% or isDDH > 70%). Two clades (four subclades) were identified among 90 genomes with the phylogenetic analysis. The phylogenetic tree indicated these 90 genomes exhibited a high intra-species genomic diversity. No clustering was assorted with the host or geographic location among these genomes. Aminoglycoside resistance genes, such as aph(2’’)-Ih, AAC(6’)-Ie-APH(2’’)-Ia, aac(6’)-IIa, ant(6), and streptothricin resistance gene SAT-4 were detected in the chromosomes from a third of the Chinese strains. Virulence-related genes were identified in all the sequenced strains. A novel large multiple drug-resistant plasmid (named pCNAC48 with 161,992 bp in length) was identified in strain ICDCAC48. Two antibiotic-resistance islands were found in the plasmid with lengths of 7,950 and 25,137 bp and G + C content of 38.23 and 32.39%, respectively. The drug resistance genes and some transposable elements were cross-distributed among the islands in the plasmid. Antimicrobial susceptibility tests indicated these resistance genes in the plasmid were functional. Plasmid conjugation and curing experiments proved pCNAC48 was stable in strain ICDCAC48. It was the first identified multiple drug resistance plasmid in A. cryaerophilus-like.